Understanding the scattering data from cone penetration tests based on sedimentary facies - Youkou Dong; Kuanjun Wang; Kanmin Shen; Lan Cui (Journal of Rock Mechanics and Geotechnical Engineering)
Cone penetration testing (CPT) and its variant with pore pressure measurements (CPTu) are versatile tools that have been traditionally used for in situ geotechnical site investigations. These investigations are among the most challenging yet indispensable tasks, providing a crucial reference for infrastructure planning, design and construction. However, data obtained through the CPT/CPTu testing often exhibit significant variability, even at closely spaced test points. This variability is primarily attributed to the complex mineral compositions and sedimentary process of the Quaternary sediments. Problems induced by the scattering data include the difficulties in estimating the shear strength of the sediments and determining the appropriate bearing stratum for pile foundations. In this paper, the conventional interpretation methods of the CPT/CPTu data are enhanced with sedimentary facies knowledge. The geotechnical investigation mainly involves 42 CPTu tests (39 essential data sets available) and 4 boring samples. Sediment types are interpreted from the CPTu data and calibrated by the nearby boring samples. Sedimentary facies are derived from the interpreted sequence stratigraphy, for which the interpretation skills are summarized in the form of characteristic curves of the CPTu data. Scattering distribution of the sediment types and their mechanical parameters are well explained by the sedimentary facies. The sediments are then categorized into a few groups by their sedimentary facies, resulting in reduced uncertainties and scattering in terms of shear strength. Bearing stratum of pile foundations is also suggested based on the sedimentary regulations.